A control method to improve the efficiency of a softswitching non-isolated bidirectional DC-DC converter for hybrid and plug-in electric vehicle applications. (1st January 2014) - Jiang, Lei; Mi, Chris; Li, Siqi; Yin, Chengliang
Hybrid energy storage system (HESS) can be adopted in hybrid, plug-in hybrid, and pure electric vehicles (HEV, PHEV, and EV), where a bidirectional DC-DC converter (BDC) is used to connect batteries and ultracapacitors. The efficiency improvement of the BDC is beneficial to increase the efficiency viability of HESS. Due to ZVS, high efficiency can be obtained at heavy load operations while the efficiency is low at light load operations mainly because of the conduction losses of the auxiliary circuits. These losses can be reduced by optimising the switching frequency. The relationship of efficiency and switching frequency are presented and discussed. A scaleddown 1 kW BDC prototype is built to verify the feasibility of the efficiency improvement. With the aim of achieving ZVS conditions and variable frequency control, the implementing method is proposed. The simulated results are also presented, which can validate the feasibility of the proposed control method.